New treatment sequence protocol to reconstruct locally advanced breast cancer. Issue 9 (15th March 2013) - Tansley, Patrick; Ramsey, Kelvin; Wong, Shirley; Guerrieri, Mario; Pitcher, Meron; Grinsell, Damien
Abstract: Background: Current treatment for locally advanced breast cancer (LABC) includes neoadjuvant chemotherapy and post‐mastectomy radiotherapy, which may be deleterious for immediate reconstruction. A few trials have instead combined neoadjuvant chemotherapy followed by preoperative radiotherapy. If safe and oncologically efficacious, mastectomy with immediate free autologous reconstruction (transverse rectus abdominis myocutaneous (TRAM)/deep inferior epigastric perforator (DIEP) flap) could then achieve a shorter, simpler reconstructive journey with better cosmesis. No trials have been performed combining this neoadjuvant regime with free autologous reconstruction as an assessment end point. Methods: We performed a Pubmed/Medline search for oncological efficacy of neoadjuvant chemotherapy followed by preoperative radiotherapy and flap reconstruction of the breast. A new treatment sequencing protocol is proposed in which patients suitable for neoadjuvant chemotherapy followed by preoperative radiotherapy and likely mastectomy are selected. Positive chemotherapeutic response is followed by radiotherapy then surgery within 6 weeks comprising mastectomy/axillary clearance and immediate reconstruction (TRAM/DIEP). Non‐responders are offered mastectomy, tissue expander reconstruction, adjuvant radiotherapy then delayed autologous reconstruction. Local/systemic recurrence rates, disease‐free survival, complications, patient satisfaction and aesthetics are examined. Results: Between 1995 and 2012, 10 trials treated LABC patients using combined neoadjuvant chemotherapy followed by preoperative radiotherapy. Compared with chemotherapy alone, increased complete pathological response, complete clinical remission, median survival and tumour‐free survival were observed. Discussion: Our new treatment sequence protocol offers a simpler, more advantageous approach to LABC. We hypothesize equivalent oncological efficacy, optimized oncological management and surgical planning. The aim was to shorten and simplify the reconstructive journey through a single operation including gold‐standard reconstruction, offering better cosmesis, fewer complications and reduced costs.